PROSTAR-UNICEF Youth Centres, Kedah November 2006 (Malaysia : UNICEF, 2006)
In 2004, Her Highness The Princess of Kedah launched the first PROSTAR-UNICEF Youth Centre in Pendang, Kedah. An initiative by the Ministry of Health and UNICEF Malaysia, the Youth Centres use the motto,'Action by Youth, for Youth and through Youth' and focus on HIVAIDS prevention through youth-friendly activities and peer-to-peer education while providing leadership opportunities for young people.
narration by Celina Khor, UNICEF Malaysia Goodwill Ambassador & 3R TV Host
dvd format
Keywords: HIV infections -- Malaysia -- Prevention